Perumusan Strategi Samudra Biru Strategic Business Unit Express PT XYZ Periode 2021–2023 - Fitriani, Dieni; Firdaus, Muhammad Ihsan; Phangestu, Joni (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
The courier, express, and parcel (CEP) market in Indonesia is growing rapidly in line with the growth of e-commerce. These developments created intense competition among the CEP companies. SBU expresses PT. As a new CEP company, XYZ seeks to avoid the red ocean competition by innovating the Blue Ocean Strategy. The research method used is qualitative research to study social phenomena by processing data in words sourced from interviews and studies of company documents and articles from outside the company. Based on the blue ocean strategy analysis, PT. XYZ formulates the company's strategy by creating B2C (Business to Customer) and C2C (Customer to Customer), and B2B (Business to Business) business models. The formulation of the blue ocean strategy for CEP services for B2C and C2C, is delivery via 3D printing, eco-friendly packaging, drop off drive-thru, mobile outlets and halal logistics services. Meanwhile, for B2B, is  special handling for special goods, halal logistics services, environmentally friendly packaging, on-time delivery, and  logistics consulting services.